Offshoring, employment, labour market reform and inequality: modelling the German experience - Society for the Study of Economic Inequality, Palma de Mallorca; Beissinger, Thomas; Chusseau, Nathalie; Hellier, Joel (Palma de Mallorca, 2014)
"A usual interpretation of the high performance of the German economy since 2006 is that the Hartz labour market reforms have boosted German competitiveness, resulting in higher exports, higher production and lower unemployment. We start from the diagnosis that this explanation is at odds with the sequence of observed facts. We propose and model an alternative scenario in which offshoring explains the gains in competitiveness but increases unemployment and inequality, and the subsequent labour market reforms lower unemployment by lessening the reservation wage and expanding the non-tradable sector, amplifying the rise in inequality. The model outcomes are consistent with all the developments of the German economy since 1995: 1) The model explains why Germany offshored earlier and more intensively than other Eurozone countries; 2) The increase in competitiveness and in the exports/production ratio occurs before the setting of the labour market reform, and this comes with both higher inequality and higher unemployment; 3) The setting of the labour market reform reduces unemployment and increases production, and this comes with a decrease in the exports/production ratio and an increase in inequality. We finally discuss (i) the possible extension of this `strategy' to other Eurozone countries, and (ii) alternative policies that act through similar mechanisms, but without increasing inequality."